Dry matter production, morphology and nutritive value of Dactylis glomerata growing under different light regimes - Peri, Pablo Luis; Lucas, R.J.; Moot, Derrick (Springer Nature, 2025)
Plant growth, morphology and nutritive value under shade can differ between temperate grasses. Therefore, the aim of this study was to quantify the dry matter (DM) production, sward morphology, crude protein (CP%), organic matter digestibility (OMD) and macro-nutrient concentrations (P, K, Mg, Ca and S) in a grazed cocksfoot (Dactylis glomerata L.) pasture under 10-year-old Pinus radiata D. Don forest. Four levels of light intensity were compared: full sunlight (100% photosynthetic photon flux density-PPFD), open + wooden slats (∼43% PPFD), trees (∼58% PPFD) and tree + slats (∼24% PPFD). The mean total DM production was 8.2 t DM ha−1 yr−1 in the open and 3.8 t DM ha−1 yr−1 in the trees + slats treatment. The changes in cocksfoot leaf area index (LAI) were related to variations in morphological aspects of the sward such as canopy height and tiller population. CP% increased as PPFD declined with mean values of 18.6% in open and 22.5% in the trees + slats treatment. In contrast, the intensity of fluctuating shade had little effect on OMD with a mean value of 79 ± 3.2%. The mean annual macro-nutrient concentrations in leaves increased as the PPFD level declined mainly between the open and the trees + slats treatments. It therefore appears that heavily shaded dominant temperate pastures in silvopastoral systems limit animal production per hectare through lower DM production rates and per animal through reduced pre-grazing pasture mass of lower bulk density from the etiolated pasture.